Determining Conjugate Points of An Aerial Photograph Stereopairs Using Separate Channel Mean Value Technique - Andri Hernandi; D. Muhally Hakim; Irawan Seomarto; Agung Budiharto; Emalia Emalia (Journal of Engineering and Technological Sciences, 2009)
In  the  development  of  digital  photogrammetric  system,  automatic image matching process play an important role. The automatic image matching is  used  in  finding  the  conjugate  points  of  an  aerial  photograph  stereopair automatically.  This  matching  technique  gives  quite  significant  contribution especially  in  the  development  of  3D  photogrammetry  in  an  attempt  to  get  the exact and precise topographic information during the stereo restitution. There are two image matching methods that have been so far developed, i.e. the area based system  for  gray  level  environment  and  the  feature  based  system  for  natural feature  environment.  This  research  is  trying  to  implement  the  area  based matching  with  normalized  cross  correlation  technique  to  get  the  correlation coefficient between the spectral value of the left image and its pair on the right. Based  on  the  previous  researches,  the  use  of  color  image  could  increase  the quality  of  matching.  One  of  the  color  image  matching  technique  is  known  as Separate Channel Mean Value. In order to be able to see the performance of the technique, a number of sampling areas with various different characteristics have been  chosen,  i.e.  the  heterogeneous,  homogeneous,  texture,  shadow,   and contrast. The  result  shows  the  highest  similarity  measure  is  obtained  on  heterogeneous sample area at size of all reference and search image, i.e. (11 pixels x 11 pixels) and   (23  pixels  x  23  pixels).  In  these  area  the  correlation  coefficient  reached more than 0.7 and the highest percentage of similarity measure is obtained. The average of total similarity  measure of conjugate images in the sampling image area  only  reach  about  41.43  %  of  success.  Therefore,  this  technique  has  a weakness and some treatment to overcome the problems is still needed.